The money array; or, show me the debtor - Samuel Allen Chambers (Finance and Society, 2023)
Money is neither a thing nor a concept. Rather, as many writers have rightly suggested, money is a relation. But what kind of relation? This articles refuses the now seemingly common-sense notion that money is an 'institution' or a 'public good'. Instead, it insists on specifying money as a concrete relation between creditor and debtor. To grasp money in both its practical and conceptual complexity, we must see it as an array. The money array is comprised of four elements: (1) a token that symbolizes the money relation; (2) a creditor who holds the token; (3) a debtor on whom the token makes a claim; (4) a denomination, i.e., the named quantity of credit/debt. The money array makes clear that no form of the money stuff - as money, i.e., as part of the money relation - ever possesses any positive, intrinsic value. The raison d'être of the money stuff - of any coin, note, bill, check, or digital token - is not to contain, have, or incarnate value. Money has no value. The value element of the money relation never lies in the money stuff, but rather can only be located across the entire money array.
Keywords: 300; bank money; credit; crypto; debt; derivatives; Monney array